2019
DOI: 10.3390/jcm8091421
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preservation Temperature on Liver, Kidney, and Pancreas Tissue ATP in Animal and Preclinical Human Models

Abstract: The recent advances in machine perfusion (MP) technology involve settings ranging between hypothermic, subnormothermic, and normothermic temperatures. Tissue level adenosine triphosphate (ATP) is a long-established marker of viability and functionality and is universal for all organs. In the midst of a growing number of complex clinical parameters for the quality assessment of graft prior to transplantation, a revisit of ATP may shed light on the underlying reconditioning mechanisms of different perfusion temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 60 publications
(99 reference statements)
3
27
0
Order By: Relevance
“…Branchereau et al demonstrated that whilst using a hypothermic oxygenated continuous circuit at 25 mmHg for 24 h, none of the pancreas grafts used in the study showed signs of, or produced markers of, cellular injury, oedema, or necrosis. The tissue level of adenosine triphosphate (ATP) is a long-established marker of graft viability and functionality and is universal for all solid organ transplants (22). ATP is also a marker of the viability of machine-perfusion treated grafts (23).…”
Section: The Rationale Of Organ Preservation By Machine Perfusionmentioning
confidence: 99%
“…Branchereau et al demonstrated that whilst using a hypothermic oxygenated continuous circuit at 25 mmHg for 24 h, none of the pancreas grafts used in the study showed signs of, or produced markers of, cellular injury, oedema, or necrosis. The tissue level of adenosine triphosphate (ATP) is a long-established marker of graft viability and functionality and is universal for all solid organ transplants (22). ATP is also a marker of the viability of machine-perfusion treated grafts (23).…”
Section: The Rationale Of Organ Preservation By Machine Perfusionmentioning
confidence: 99%
“…The findings show that the re-introduction of tissue adenosine triphosphate (ATP) levels in the current method may be valuable for improving the viability assessment of organs that are harvested for transplantation. 36 These findings may help with future investigations. Our purpose was to investigate each of these molecules (erythropoetin, sildenafil, lazaroid, and octreotide), and based on the results, to design further studies.…”
Section: Discussionmentioning
confidence: 88%
“…The ischemic phase already primes the tissue for the subsequent damage [7]. Reducing equivalents are generated to provide electrons for RET, which are in turn required for mROS production upon subsequent reperfusion [9,12,13]. The predominant mitochondrial metabolite accumulating during ischemia is driven by the reverse operation of succinate dehydrogenase (SDH).…”
Section: Sources Of Rosmentioning
confidence: 99%
“…The temperature is low enough to achieve sufficient oxygenation without the implicit addition of an oxygen carrier, which enables the restoration of ATP levels. At the same time, the temperature is high enough to allow for the partial viability assessment of the organ [13,43,44].…”
Section: Subnormothermic Machine Perfusion (Snmp) At 20-25 • Cmentioning
confidence: 99%
See 1 more Smart Citation